Guy L. Beck (ed.). Alternative Krishnas. Regional and Vernacular Variations on a Hindu Deity - Śliwczyńska, Bożena (Acta Orientalia Vilnensia, 2007)
Guy L. Beck (ed.). Alternative Krishnas. Regional and Vernacular Variations on a Hindu Deity, Albany: State University of New York Press, 2005, pp. xvi+217. IS BN 0-7914-6415-6 (HB)